Penentuan Daerah Prospek Logam Tanah Jarang di Pulau Singkep - Ngadenin; Karunianto, Adhika Junara; Indrastomo, Frederikus Dian (EKSPLORIUM, 2020)
Rare earth elements (REE) are strategic material used in high-tech and clean energy devices. In Indonesia, REE contained in monazite, zircon, and xenotime minerals as accessories minerals in tin mining located in the granite tin belt of Riau Islands to Bangka Belitung. Singkep is one of the potential areas of REE because its location is in the granite tin belt. The goal of the study is to determine the REE prospects in Singkep Island. The method used by taking 25 pan concentrated samples on some tailing ex tin mining on the Singkep island. These samples were taken from each rock formation on Singkep Island in sequence from older to younger rocks formation, respectively. They are Permian Carboniferous of Bukit Duabelas quartzites, Permian Carboniferous of Persing Metamorphic Rocks, Triassic Muncung granite, Jurassic Tanjungbuku granite, Holocene swamps deposits and alluvium. Each sample of pan concentrated is divided into two parts for REE content and grain mineral analysis. All 25 samples were analyzed for REE content, while only 14 samples for the grain mineral. The results of REE content and grain mineral analysis indicate that the REE prospect area located in the tailings ex tin mining in the rock formation of the Muncung granite area. The highest concentration of lanthanum reached 20100 ppm, cerium 37100 ppm, yttrium 9872 ppm, and neodymium 2840 ppm in monazite, zircon, and allanite.